Edukasi Kesehatan Menggunakan Media Video terhadap Pengetahuan dan Sikap Pemberian ASI Eksklusif pada Ibu Hamil Trimester III di Palangka Raya - Neneng Safitri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
A low rate of exclusive breastfeeding is a threat to child development. According to the Ministry of Health 2018, exclusive breastfeeding in Indonesia in 2017 was 35.7%, while in Palangka Raya, it was 14.9%. One of the factors causing a low rate of exclusive breastfeeding is the mother’s poor knowledge and attitude. They were determining the effectiveness of the health education using video to improve the knowledge and attitude on exclusive breastfeeding among pregnant women in the 3rd trimester III in the working area of Pahandut Public Health Center, Palangka Raya. The research type was quasi-experiment with a control group design pre-test-post test. The research population and sample were 69 pregnant women in the 3rd trimester in the working area of Pahandut Public Health Center, Palangka Raya, sampled using a simple random sampling technique. The video development used the Thiagarajan theory, which has been validated by a multimedia expert, learning expert, and midwifery expert. The data collection used a questionnaire. The data analysis used General Linear Model (GLM). The research result showed improvement before and after treatment using video with a difference of 14 points in knowledge and 16 in attitude. There was significant improvement in knowledge using video (F=275.727; sig=0.00; partial eta=0.80) and attitude (F=370.015; sig=0.00; partial eta=0.84). Video improves knowledge and attitude on exclusive breastfeeding.